Plática as Critical Instruction: Talking With Bilingual Students About Their Reading - Leila Flores-Dueñas (Educational Considerations, 1999)
Throughout the time that I taught in elementary schools, I observed how countless bilingual learners were exited from language programs into all-English speaking classrooms as early as the 2nd grade.